Camphor Plasmid-Mediated Chromosomal Transfer in Pseudomonas putida - Shaham, M. (1973)
Camphor-utilizing strains of Pseudomonas putida have been shown to carry the genetic information required for camphor degradation on a plasmid. The plasmid-carrying strains can serve as donors of both plasmid-borne and chromosomal genes. As recipients, plasmid-deleted strains are much superior to those carrying the camphor pathway genes. The transfer frequency of chromosomal, but not plasmid-borne, genes is markedly enhanced if the donor cells are irradiated with ultraviolet light followed by 3-h of growth on a rich medium in the dark. Recombinants selected for prototrophy are stable and most acquire the camphor (CAM) plasmid concomitantly; only a few of the Cam(+) recombinants inherit the donor's ability to transfer chromosomal genes at a high frequency. Transfer-defective mutations occur on the CAM plasmid, affecting both CAM and chromosomal gene transfer.